Whether Chinese Primary School English Teacher Are Able to Help Students Learn With a Deep Approach (Asian Education Studies, 2022)
In order to improve the quality of education, there is a great concern for students‟ learning methods. Students‟ learning methods are basically divided into deep and surface methods. The deep approach is seen as the one that is encouraged to be used. However, in the views of the researchers, students in Asian countries tend to prefer to use surface methods of learning. Therefore, the authors would like to critically analyse an innovative teaching activities in a Chinese primary school to investigate whether Chinese primary school English teachers might be able to help their students achieve deep learning through changes in their classrooms.